(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2018)
Abstract | The 1960s was the decade in which satellite technology was introduced to the television world via a series of live broadcasts. With the active participation of 46 stations, BBC’s Our World (1967) was undoubtedly the most globally far-reaching of them all. Conceived around Marshall McLuhan’s concept of the communicative global village, the special program took full advantage of satellites to reach a truly global audience and use the occasion to announce the dawn of globalization and what living in a small and thoroughly connected world would mean for its inhabitants. Prominent in the broadcast was the program’s Canadian segment, which aired right after the introduction and included an interview with Marshal McLuhan in the Canadian Broadcasting Corporation’s studio in Toronto. This paper considers McLuhan’s contributions both to the ideas and practices of planetary communication as well as his direct involvement with the production of Our World. I demonstrate how McLuhan’s understanding of the co-constitution of time and space not only set live television broadcasts apart from other temporal media but that, through these spatiotemporal affinities, One World can be considered to belong to the prehistory of our contemporary telecomputational technologies such as the Internet and mobile phones. Résumé | Les années 1960 ont été la décennie où la technologie satellitaire a été introduite dans le monde de la télévision par le biais d’une série d’émissions en direct. Avec la participation active de 46 stations, Our World (1967) de la BBC a été sans aucun doute été l’émission la plus diffusée à travers le monde. Conçu autour du concept du village planétaire de communication de Marshall McLuhan, le programme spécial a profité pleinement des satellites pour atteindre un public véritablement mondial et a saisi l’occasion pour annoncer l’aube de la mondialisation et ce que vivre dans un monde petit et complètement connecté signifierait pour ses habitants. Le segment canadien du programme, diffusé juste après l’introduction, a été mis en vedette et comprenait une entrevue avec Marshall McLuhan dans le studio de la Société Radio-Canada à Toronto. Cet article considère les contributions de McLuhan aux idées et aux pratiques de la communication planétaire, mais aussi son implication directe dans la production d’Our World. Je démontre comment la compréhension de McLuhan de la co-constitution du temps et de l’espace non seulement sépare les émissions télévisées en direct des autres médias temporels, mais aussi, par ces affinités spatio-temporelles, comment One World peut appartenir à la préhistoire de nos technologies de télécommunication contemporaines comme Internet et les téléphones mobiles.